2021
DOI: 10.3389/fnut.2021.761631
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Enhancer, the Latest Evidence of Rikkunshito

Abstract: Rikkunshito is a Japanese herbal medicine (Kampo) that has been attracting attention and researched by many researchers not only in Japan but also worldwide. There are 214 rikkunshito articles that can be searched on PubMed by August 2021. The reason why rikkunshito has attracted so much attention is due to an epoch-making report (Gastroenterology, 2008) discovered that rikkunshito promotes the secretion of the orexigenic peptide ghrelin. Since then, many researchers have discovered that rikkunshito has a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…It is synthesized from gastric mucosa and secreted into the blood. There are two main forms: acylated ghrelin and deacylated ghrelin [ 53 , 54 ]. The increasing evidence indicates that ghrelin plays an important role in NAFLD [ 55 , 56 ].…”
Section: The Role Of Autophagy and Pyroptosis In Liver Disordersmentioning
confidence: 99%
“…It is synthesized from gastric mucosa and secreted into the blood. There are two main forms: acylated ghrelin and deacylated ghrelin [ 53 , 54 ]. The increasing evidence indicates that ghrelin plays an important role in NAFLD [ 55 , 56 ].…”
Section: The Role Of Autophagy and Pyroptosis In Liver Disordersmentioning
confidence: 99%
“…ISL is not only detected after the oral administration of TJ-43, but a comparable amount of ISL is also shown in plasma and brain distribution, especially compared with an ISL (5 mg~50 mg/kg) single treatment [94]. Magomi et al suggest that ISL is one of the most important active components in TJ-43, acting as an antagonist to both CRF receptor 1 (CRFR1) and serotonin 2C receptor (5-HT2CR) in order to reduce ghrelin secretion, which further improves stressinduced anorexia [94,95,99]. In addition, several multi-center, double-blinded, randomized placebo-controlled studies were conducted to examine its effect with regard to improvements in upper GI disorders, such as dyspepsia [100][101][102][103].…”
Section: Tj-43mentioning
confidence: 99%
“…Even with a standard treatment, a three-drug combination of a 5-HT3 receptor antagonist, a neurokinin-1 receptor antagonist, and dexamethasone (as an aprepitant regimen) show only a 60~80% mitigation of CINV [107]. Seeking further improvement in CINV, some clinical studies recommend the co-administration of TJ-43 as an effective option for breakthrough CINV, as TJ-43 also acts as an antagonist at the 5-HT2B/C, 5-HT3 receptors and the ghrelin receptor [95,99,[108][109][110]. TJ-43 combined with chemotherapy is shown to prevent CINV in esophagus, gastric, lung, cervical, and corpus cancer patients [111][112][113][114].…”
Section: Tj-43mentioning
confidence: 99%
“… 10 Japanese scholars have found through experiments that cutting off the vagus nerve of rats can reduce the level of acylated ghrelin in plasma, and cisplatin can further reduce the level of acylated ghrelin and cause anorexia. 19 , 20 Subsequently, the administration of ghrelin in rats can improve the reduction of food intake caused by cisplatin. Peripheral factor ghrelin signaling pathway is the most studied in CIA, and GDF-15 related pathway has gradually entered scholars’ vision.…”
Section: Pathogenesis Of Cia: Central Nervous System Peripheral Signa...mentioning
confidence: 99%
“…In 2008, an epoch-making study by Japanese scholars found that Rikkunshito could improve appetite in a cisplatin-induced anorexia model in rats by promoting the secretion of ghrelin, which immediately attracted the attention and research of a large number of scholars. 19 , 20 Clinical study found that LJZD and modified LJZD improved tumor-associated anorexia effectively. 18 , 21–33 A number of animal experiments have also proved that this prescription has the efficacy of preventing and treating tumor-associated anorexia.…”
Section: Introductionmentioning
confidence: 99%